Increasing Legal Awareness of Waste Bank in Bekasi, Indonesia: How can legal counsel make a difference for environmental sustainability? - Siombo, Marhaeni Ria; Triatmodjo, Michael Harjo (Universitas Negeri Semarang, 2022)
Waste banks have emerged as pivotal entities in promoting sustainable waste management practices, particularly in urban areas like Bekasi, Indonesia. However, their effectiveness is contingent upon a robust legal framework that supports their operations and ensures environmental sustainability. This paper examines the role of legal counsel in augmenting the efficacy of waste banks in Bekasi towards achieving environmental sustainability objectives. Through an analysis of the existing legal landscape governing waste management and waste bank operations in Bekasi, this study identifies gaps and challenges that hinder their effectiveness. Furthermore, it explores how legal counsel can provide invaluable guidance and support to waste bank operators, local communities, and relevant stakeholders. By leveraging legal expertise, waste banks can navigate regulatory complexities, address compliance issues, and advocate for policy reforms conducive to sustainable waste management practices. The paper also highlights the importance of legal education and capacity-building initiatives aimed at enhancing legal literacy among waste bank stakeholders. By empowering stakeholders with legal knowledge and support, waste banks can optimize their contributions to waste reduction, resource recovery, and environmental conservation efforts in Bekasi. Ultimately, this paper underscores the transformative role of legal counsel in advancing environmental sustainability through the operational effectiveness of waste banks in Bekasi, Indonesia, and offers insights for similar contexts globally.